ICOH International Code of Ethics for Occupational Health Professionals: Historical fortune and future perspectives in Italy - Petyx, Carlo; Costa, Giovanni; Manno, Maurizio; Valenti, Antonio; Iavicoli, Sergio (La Medicina del Lavoro, 2016)
The Working Group responsible for the Italian translation of the third edition of the International Code of Ethics, appointed by the President of the International Commission on Occupational Health (ICOH), Dr. Jukka Takala, completed last April the revision work. The final text, already available on the ICOH website, has been printed and distributed by the Italian National Institute for Insurance against Accidents at Work (INAIL) at the 79th National Congress of the Italian Society of Occupational Medicine and Industrial Hygiene (SIMLII), in Rome. The curators of this third Italian edition have accomplished the delicate task of adaptation in Italian, taking into account the specificities of the practice of medicine in the Italian work environment. It involves many professionals with diverse roles and responsibilities in the public and private sectors for safety, hygiene, health and environment in relation to work. More than twenty years after the first Italian edition, we trace the evolution of the ICOH International Code of Ethics, in order to focus its birth, national and international distribution, and continuous improvement as well as its ability to direct the stakeholders towards a participatory prevention model, in a legislative framework that has seen over the past two decades a radical change in the Italian world of work.